Membangun Penguatan Budaya Literasi Media dan Informasi dalam Dunia Pendidikan - Nur Ainiyah (Program Pascasarjana Universitas Ibrahimy, 2017)
Media literacy are the ability to know, analyze and deconstruct media image. The ability to make audience as mass media consumer like many people could know how to use mass media and social media. How mass media do contructing every information or media content to influence audience. Media literacy teach public to choose media content which is true or untrue (hoax). The knowledge of media literacy in the education world are important. Social media situation now are unclear. Netizen as social media user is always write and spread hated speech, issues and hoax to reach popularity. Negative behavior of netizens in the social media era, such as spread of untrue news (hoax), blasphemy and slander, black campaign, and various other negative behavior that every day can be found on smartphone which is a reflection of the bad behavior. This condition is sometimes exacerbated by the role of media contaminated with political interests and double standards so that only the party supporters news who get the most benefit in their message. So the knowledge of media literacy should transmit for public in the educational world.